Alterations of the gut mycobiome in patients with MS - Saumya Shah (EBioMedicine, 2021)
Background: The mycobiome is the fungal component of the gut microbiome and is implicated in several autoimmune diseases. However, its role in MS has not been studied. Methods: In this case-control observational study, we performed ITS sequencing and characterised the gut mycobiome in people with MS (pwMS) and healthy controls at baseline and after six months. Findings: The mycobiome had significantly higher alpha diversity and inter-subject variation in pwMS than controls. Saccharomyces and Aspergillus were over-represented in pwMS. Saccharomyces was positively correlated with circulating basophils and negatively correlated with regulatory B cells, while Aspergillus was positively correlated with activated CD16+ dendritic cells in pwMS. Different mycobiome profiles, defined as mycotypes, were associated with different bacterial microbiome and immune cell subsets in the blood. Initial treatment with dimethyl fumarate, a common immunomodulatory therapy which also has fungicidal activity, did not cause uniform gut mycobiome changes across all pwMS. Interpretation: There is an alteration of the gut mycobiome in pwMS, compared to healthy controls. Further study is required to assess any causal association of the mycobiome with MS and its direct or indirect interactions with bacteria and autoimmunity. Funding: This work was supported by the Washington University in St. Louis Institute of Clinical and Translational Sciences, funded, in part, by Grant Number # UL1 TR000448 from the National Institutes of Health, National Center for Advancing Translational Sciences, Clinical and Translational Sciences Award (Zhou Y, Piccio, L, Lovett-Racke A and Tarr PI); R01 NS102633-04 (Zhou Y, Piccio L); the Leon and Harriet Felman Fund for Human MS Research (Piccio L and Cross AH). Cantoni C. was supported by the National MS Society Career Transition Fellowship (TA-1805-31003) and by donations from Whitelaw Terry, Jr. / Valerie Terry Fund. Ghezzi L. was supported by the Italian Multiple Sclerosis Society research fellowship (FISM 2018/B/1) and the National Multiple Sclerosis Society Post-Doctoral Fellowship (FG- 1907-34474). Anne Cross was supported by The Manny & Rosalyn Rosenthal-Dr. John L. Trotter MS Center Chair in Neuroimmunology of the Barnes-Jewish Hospital Foundation. The content is solely the responsibility of the authors and does not necessarily represent the official views of the National Institutes of Health.